2015
DOI: 10.1177/1464993414546980
|View full text |Cite
|
Sign up to set email alerts
|

Curbing corruption, financial development and income inequality

Abstract: In recent years, many of the Commonwealth countries have experienced a reduction in income inequalities due to the development of financial markets and intermediaries. at the same time, widespread corruption among public officials, civil servants, or politicians from these countries have been well documented. a key public policy question is whether the return to financial sector development at the level of massive corruption, exacerbate income inequality, offsetting the benefits of financial development. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 43 publications
9
48
1
2
Order By: Relevance
“…First, the intensive margin theory maintains that output is promoted by financial access through both direct and indirect mechanisms in order to reward businesses that are already engaged with formal banking services (Chipote, Mgxekwa & Godza, 2014). Second, from the framework of the extensive margin theory, enhancing financial access goes beyond benefiting existing users of formal financial services to equally rewarding previously excluded fractions of the population (Holtz-Eakin, Joulfaian & Rosen, 1994;Batabyal & Chowdhury, 2015;Evans & Jovanovic, 1989;Black & Lynch, 1996;Bae, Han & Sohn, 2012;Odhiambo, 2014;Chiwira, Bakwena, Mupimpila & Tlhalefang, 2016;Orji, Aguegboh & Anthony-Orji, 2015). Put in other terms, the framework of the extensive margin theory maintains that access to finance could also be benefitical to households and business segments that were not previously involved in formal banking operations.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…First, the intensive margin theory maintains that output is promoted by financial access through both direct and indirect mechanisms in order to reward businesses that are already engaged with formal banking services (Chipote, Mgxekwa & Godza, 2014). Second, from the framework of the extensive margin theory, enhancing financial access goes beyond benefiting existing users of formal financial services to equally rewarding previously excluded fractions of the population (Holtz-Eakin, Joulfaian & Rosen, 1994;Batabyal & Chowdhury, 2015;Evans & Jovanovic, 1989;Black & Lynch, 1996;Bae, Han & Sohn, 2012;Odhiambo, 2014;Chiwira, Bakwena, Mupimpila & Tlhalefang, 2016;Orji, Aguegboh & Anthony-Orji, 2015). Put in other terms, the framework of the extensive margin theory maintains that access to finance could also be benefitical to households and business segments that were not previously involved in formal banking operations.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Corruption indices often exhibit a strong correlation with macro‐level inequality measures such as Gini‐coefficient. Countries with lower levels of inequality tend to have lower levels of corruption (Batabyal & Chowdhury, ; Gupta, Davoodi, & Alonso‐Terme, ). Because the transition of more people from poverty into the middle class represents a reduction in inequality, this might support the argument that the middle class is the driver of mobilization against corruption.…”
Section: The Role Of the Middle Classmentioning
confidence: 99%
“…Some empirical studies (Beck et. al., 2007;Shahbaz and Islam, 2011) revealed that financial development had affected income inequality negatively, while some recent studies (Batabyal and Chowdhury, 2015;Denk and Cournède, 2015) have found that financial development affected income inequality positively. Furthermore, some studies suggested that the finance-inequality relationship follows a U or an inverted U curve (Greenwood and Jovanovic, 1990).…”
Section: Review Of Empirical Literaturementioning
confidence: 99%